M-fractional solitons and periodic wave solutions to the Hirota-Maccari system - Sulaiman, Tukur Abdulkadir; Yel, Gulnur; Bulutt, Hasan (World Scientific Publ Co Pte Ltd, 2019)
In this study, we construct several wave solutions to the nonlinear fractional Hirota-Maccari equation with a truncated M-fractional derivative via the extended sinh-Gordon equation expansion method. The constraint conditions that guarantee the existence of valid solutions are stated. We use suitable values of parameters in plotting the 2- and 3-dimensional graphs of the reported solutions.
Keywords: M-fractional derivative; Hirota-Maccari equation; soliton